Impact of Chemotherapy on Venous Thromboembolism in Cervical Cancer: Systematic Meta-Analysis Observational Studies - Fitriyadi Kusuma; Kemal Akbar Suryoadji; Wulyo Rajabto; Geraldus Sigap Gung Binathara; Shuffa Chilla Mayhana; Fahrayhansyah Muhammad Faqih; Bintang Wirawan; Abdul Hafiidh Surya Putra (Jurnal Kesehatan Cendikia Jenius, 2026)
Objective: Cervical cancer is associated with an increased risk of venous thromboembolism (VTE), which may be further aggravated by chemotherapy. This study aimed to assess the impact of chemotherapy on VTE incidence in patients with cervical cancer. Methods: A systematic review was conducted according to PRISMA 2020 guidelines. PubMed, the Cochrane Library, and EMBASE were searched from inception to October 2024 for observational studies reporting VTE incidence in cervical cancer patients receiving chemotherapy. Studies including women with cervical cancer treated with chemotherapy and reporting VTE outcomes were eligible, while studies evaluating radiotherapy or surgery alone were excluded. Results: Three observational studies involving 2,292 patients met the inclusion criteria. Pooled analysis showed that chemotherapy significantly increased VTE risk (RR 2.83; 95% CI: 2.05–3.90; p < 0.001), with low statistical heterogeneity. The reported incidence of chemotherapy-associated VTE ranged from 10.0% to 18.7%. Conclusion: Chemotherapy is associated with a nearly threefold increased risk of VTE in cervical cancer patients. These findings support routine VTE risk stratification prior to chemotherapy and consideration of individualized thromboprophylaxis. Further prospective studies are needed to define optimal prevention strategies.